2020
DOI: 10.1007/s40620-020-00717-0
|View full text |Cite
|
Sign up to set email alerts
|

Contraception in chronic kidney disease: a best practice position statement by the Kidney and Pregnancy Group of the Italian Society of Nephrology

Abstract: Even though fertility is reduced, conception and delivery are possible in all stages of CKD. While successful planned pregnancies are increasing, an unwanted pregnancy may have long-lasting deleterious effects, hence the importance of birth control, an issue often disregarded in clinical practice. The evidence summarized in this position statement is mainly derived from the overall population, or other patient categories, in the lack of guidelines specifically addressed to CKD. Oestroprogestagents can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 134 publications
0
14
0
Order By: Relevance
“…Counseling should be repeated after transplantation [14]. Emergency contraception with high dose progestins or intrauterine devices is not contraindicated, but it should be avoided whenever possible, even if far preferable to abortion [15].…”
Section: Planning Posttransplant Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Counseling should be repeated after transplantation [14]. Emergency contraception with high dose progestins or intrauterine devices is not contraindicated, but it should be avoided whenever possible, even if far preferable to abortion [15].…”
Section: Planning Posttransplant Pregnancymentioning
confidence: 99%
“…In summary, despite the risk of several complications, single-center and registry reports [69][70][71][72][73][74] and a meta-analysis [75] found that pregnancies in kidney transplant recipients with normal kidney function did not affect short-term and long-term patient and graft survival. However, the risk of graft dysfunction during pregnancy or in the postpartum period may be elevated in patients who became pregnant early after transplantation [14][15][16][17] and in those with elevated levels of serum creatinine [76,77]. A word of caution may concern the long-term impact on a patient who develops preeclampsia.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Pre-pregnancy counseling discussing the effect of pregnancy on kidney disease and the impact of kidney disease on maternal and fetal outcomes in kidney transplant recipients is imperative. It is of paramount importance that pregnancies are planned, and effective methods of contraception are provided to women with history of kidney transplants to ensure that pregnancies do not occur prior to maternal optimization [7,8]. Nephrologists do not usually discuss contraception with their female patients of childbearing age [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…7 Use of an IUD is also reportedly low in kidney transplants recipients, although the efficacy and safety of IUDs in this population have only recently been established. 8,9 Respondents in our survey were heterogeneous in regard to underlying disease type and stage of chronic kidney disease. Beyond LARC, other forms may be acceptable based on desire for future pregnancy and consideration of side effect profiles.…”
Section: Discussionmentioning
confidence: 99%
“…For individuals with proteinuria and/or hypertension, progestin-only pills provide a safer cardiovascular profile than those containing estrogen, but are subject to user error given the daily timing of use required. 9 It was interesting that about 1 in 3 women endorsed use of 2 or more methods in the past 12 months, which could indicate fragmented or discontinued use. Unfortunately, our survey was not designed to determine whether methods were used together or in succession.…”
Section: Discussionmentioning
confidence: 99%